Selfie Photo Spot Development of Naga Sopa Swimbath Tourism Realizes Community Welfare - Dardanila; Susilo, Hariadi; Suwilo, Saib; Tulus; Bayu, Eva Sartini; Tafsin, Ma’ruf; Patriani, Peni; Tugiman; Ariani, Farida; Silalahi, Amlys Syahputra (Talenta Publisher, 2021)
The arrangement of selfie photo spots is expected to increase the target of tourist visits, both foreign and local. Therefore, making selfie photo spots will be used as a promotional medium to increase the number of tourist visits. Sweembath Bahapal baths were built in 1930 by the Dutch government by employing plantation workers. The results of the preliminary survey indicate the need for further development so that it is expected to improve the welfare of the village community. The purpose of the activity is to become a creative and attractive place for recreation with an environmental perspective, organizing selfie photo spots which are expected to increase the target of tourist visits, both foreign and local. The method used in the implementation of the construction of eight selfie photo spots is something that provides recreational facilities that can make tourists active in tourist activities, the University of North Sumatra community service agency builds facilities for self-painted photo spots as follows (1) Dolphins, (2) Dinosaurs, (3) Elephants, (4) Butterflies, (5) Fire Tongue Wings, (6) Whales, (7) Butterflies, and (8) Turtles. Spot facilities Selfie photos form facts in the form of responses from collective or individual subjects such as 1) the presence of visitors who take advantage of the facilities, 2) parking attendants who regulate vehicle parking 3) traders who sell types of merchandise products, 3) place rental, mats, buoys, and changing rooms. The impact of the development and improvement of the functions of the facilities and infrastructure above, affects the welfare of the community, managers and traders in the Sweembath environment.